2001
DOI: 10.1159/000048850
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Disease in Siblings of Patients with Hereditary Hemochromatosis

Abstract: Background: Parents of hereditary hemochromatosis (HH) homozygote patients, who are predominantly HH heterozygotes, have been found to have an increased risk of colonic neoplasia, diabetes, stroke death, stomach cancer and leukemia. The health histories of siblings of HH patients are reported. Methods: Individuals homozygous for HH were mailed questionnaires concerning the health histories of their siblings. Spouses of the HH homozygotes were asked to complete accompanying questionnaires concerning their sibli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…9 Previous studies have assessed the value of a family history in the initial diagnosis of hemochromatosis 10 and the risk of hemochromatosis and associated conditions in siblings of hemochromatosis probands. 11 However, the accuracy of self-reported family history of H/IO (analytic validity), or the value of such reports in predicting the risk that family members will develop H/IO (clinical validity), has not been reported. A preliminary investigation of the Hemochromatosis and Iron Overload Screening (HEIRS) study indicated that self-reported family history of H/IO may aid in identifying participants at high risk to have HFE C282Y homozygosity.…”
mentioning
confidence: 99%
“…9 Previous studies have assessed the value of a family history in the initial diagnosis of hemochromatosis 10 and the risk of hemochromatosis and associated conditions in siblings of hemochromatosis probands. 11 However, the accuracy of self-reported family history of H/IO (analytic validity), or the value of such reports in predicting the risk that family members will develop H/IO (clinical validity), has not been reported. A preliminary investigation of the Hemochromatosis and Iron Overload Screening (HEIRS) study indicated that self-reported family history of H/IO may aid in identifying participants at high risk to have HFE C282Y homozygosity.…”
mentioning
confidence: 99%
“…Our results for cardiomyopathy suggest that our cohort of patients indeed encompass those with a haemochromatosis phenotype (and thus also that their relatives Only three studies have assessed the risks of cardiovascular disease among close relatives of patients with phenotypic GH [19][20][21]. In two studies by Nelson et al [19,20] (including 1950 parents of 975 patients with GH and 1265 siblings of 596 patients with GH), no increased risk of heart disease was demonstrated. However, in the study by Jacobs et al [21] (including 735 first-degree relatives of 224 patients with GH), cardiovascular diseases were significantly more frequent in the first-degree relatives of patients than in the control population.…”
Section: Discussionmentioning
confidence: 68%
“…In fact, siblings and twins of probands with phenotypic haemochromatosis are known to have higher levels of iron compared with those related to probands with a haemochromatosis genotype, but not phenotype [17,18], suggesting that other factors are critical for the expression of phenotypic disease. Thus, in the context of a family history of genetic haemochromatosis (GH), the observed risks of IHD among individuals heterozygous for HFE mutations may be different from those for individuals with HFE mutations detected through population screening, but the risks of IHD in the former remain unclear [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…found no correlation between the carriage of the C282Y mutation and symptoms, including arthritis, in a study of 41 038 individuals attending an insurance‐based, well‐person screening program 8 . Several studies have suggested a link between the carriage of HFE gene mutations and the development or progression of arthritis; however, all have considered highly selected subjects 9–12 . The purpose of the present study was to determine whether HFE gene mutations in the general population are associated with an increased prevalence of arthritis.…”
Section: Introductionmentioning
confidence: 85%